Real experience of young and middle-aged hemodialysis patients: a qualitative meta-synthesis - Zhang, Kai; Teng, Zeng; Li, Ailing; Zhang, Nan; Wang, Ruixue; Wei, Shuimiao; Ni, Cuiping (Frontiers in Medicine, 2025)
BackgroundAbout 89% of global End-stage renal disease (ESRD) patients receive hemodialysis. Data show that about 40% 60% of dialysis patients are young and middle-aged. Hemodialysis significantly impacts the daily life and rehabilitation of patients, underscoring the urgency of understanding their experiences and needs. However, findings from previous individual qualitative studies may lack representativeness.AimsThis study used Meta-synthesis to offer a thorough understanding of the lived experiences, psychological states, and needs of young and middle-aged hemodialysis patients.DesignSystematic review and meta-synthesis.MethodsA systematic search was conducted in PubMed, Embase, The Cochrane Library, Web of Science, CINAHL, CBM, CNKI, WanFang, and VIP databases from the establishment of each database to November 4, 2024, targeting qualitative studies on the experiences of young and middle-aged hemodialysis patients (aged 18–65 years old). Quality assessment used the Joanna Briggs Institute’s 2016 Checklist for Qualitative Research, followed by meta-synthesis. The study’s reporting was informed by the principles of the Enhancing Transparency in Reporting the Synthesis of Qualitative Research (ENTREQ) framework. The thematic analysis approach was employed to synthesize the findings.ResultsTwenty-two studies were included, covering 14 countries. The inclusion of 22 studies yielded 83 findings, categorized into nine subthemes and condensed into four overarching themes: negative emotional experiences toward illness and hemodialysis, experience of financial problems due to long-term hemodialysis treatment, disruptions to normal life, and seeking multiple forms of support among hemodialysis patients.ConclusionHealthcare providers should attach importance to this group, to meet their specific needs, and support their active recovery. The goal is to help them relieve negative emotions, reduce financial burden, return to normal life and meet multiple forms of support.